TECHNIQUES OF TEACHING PHRASEOLOGICAL UNITS - Rzaeva, R.K.; Jienbaeva, A. (FAN va JAMIYAT, 2019)
The article is devoted to the description of effective methods of teaching phraseological units (idioms, proverbs and sayings) in English, that are a means of enriching the vocabulary. Taking as a basis the works of the prominent scholars, the author of the article recommends to use such techniques as cluster, Venn diagram, case-study, contextualization and others, that are considered to be more effective in teaching phraseological units.